FACTORS CONTRIBUTING TO INCREASE NURSING SHORTAGES AMONGST NURSES WORKING IN PRIVATE AND PUBLIC TERTIARY CARE HOSPITAL KARACHI, PAKISTAN. - Khairunnisa Khan; Samra Khalid; Asma Muhammad Ibrahim; Muqadas Muneer Ahmed; Farhat Murtaza; Laiba Satti Khursheed; Sadaf Wazir; Nazneen Bano; Srikant Mendhrani; Shahla Pardhan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To determine the factors contributing to increase nursing shortages in public and private tertiary care hospitals, Karachi Pakistan. Introduction: Nurses are a significant part of the healthcare system; however currently healthcare is suffering from shortages of nurses into their profession which leads in compromise of the patient-care system and health related outcome. Methodology: An analytical Cross-sectional study was conducted amongst 140 nurses through convenient sampling technique and self-structured questionnaire. Results: The results revealed that, shortage of nurses was identified more on female 76 (54.3%), married71 (50.7%) women whose age between 21-30 53 (37.9%), had more than 1-5 years of experience 59(42.1%) in the position of staff nurse 105(75%) who strongly agree; that shortage of nurses impact the quality of patient care 52 (37.1%), insufficient government funding59 (42.1%), limited availability of nursing education system 59 (42.1%),lack of career advancement 51(36.4%), absence of rewards and appreciation54(38.6%), staff safety 46(32.9%), lower census of nursing staff lead to increase stress and burnout among nurses 49 (35%), government, healthcare institutions, & educational bodies address the shortage of nurses51(36.4%); Public awareness about the importance and role of shortage of nurses 56 (40%), all were contributing factors which trigger or cause nurses to leave the profession or migrate into another country to avail good incentives and better opportunities. Besides, Spearman Correlation showed dependent variables are significantly associated with each other. Conclusion: The nursing profession is compromised by the shortages of bedside nurses which directly impacts on patient-care and health system of the country.